2009
DOI: 10.1097/hjh.0b013e328324eb27
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory arterial stiffness index is not correlated with the pressor response to laboratory stressors in normotensive humans

Abstract: Ambulatory arterial stiffness index (AASI) is a novel estimate of arterial stiffness which independently predicts cardiovascular mortality, even in normotensive subjects. Additionally, other markers derived from ambulatory blood pressure (BP) monitoring, including variability (BPV), pulse pressure (PP), nocturnal dipping, and morning BP surge have all been shown to be predictive of endorgan damage and cardiovascular disease. Exaggerated cardiovascular reactivity to sympathoexcitatory stimuli may also predict f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
3
10
0
1
Order By: Relevance
“…37 Similarly, AASI has been found to negatively correlate with the morning surge in diastolic BP, daytime diastolic BP, 24-h mean arterial pressure variability, and nocturnal dips in systolic BP, diastolic BP and mean arterial pressure. 31 These data are broadly consistent with the observations in the present study. Interestingly, however, the values of AASI measured in the present study were not significantly different between the dipper and nondipper groups, perhaps suggesting that although BP variability is related to AASI, dipping status is not a major determinant in patients with grade 1/grade 2 hypertension.…”
Section: Discussionsupporting
confidence: 95%
“…37 Similarly, AASI has been found to negatively correlate with the morning surge in diastolic BP, daytime diastolic BP, 24-h mean arterial pressure variability, and nocturnal dips in systolic BP, diastolic BP and mean arterial pressure. 31 These data are broadly consistent with the observations in the present study. Interestingly, however, the values of AASI measured in the present study were not significantly different between the dipper and nondipper groups, perhaps suggesting that although BP variability is related to AASI, dipping status is not a major determinant in patients with grade 1/grade 2 hypertension.…”
Section: Discussionsupporting
confidence: 95%
“…On the other hand, BRS measured based on the time domain analysis in our study was mainly modulated by cardiac parasympathetic activity [31]. Coincidently, this observation is in accordance with the finding from a recent study that AASI was not associated with BP reactivity to laboratory stressors in young and normotensive individuals [32].…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies have shown AASI be affected by the extent of the nocturnal BP fall, 3-7 BP variability expressed as the standard deviation, [12][13][14][15] and baroreflex sensitivity, 16 and therefore antihypertensive treatment which could modify these factors might in turn affect AASI in a manner independent of changes in arterial stiffness. Furthermore, previous findings, [17][18][19] taken together with the present findings, have suggested that AASI represents an integrated measure of ventriculo-arterial coupling, depending on both arterial (arterial stiffness and systemic vascular resistance) and cardiac factors (stroke volume and heart rate).…”
Section: Discussionmentioning
confidence: 98%